IoT-based Smart Home Monitoring and Automation System Using Android Application (GUB Journal of Science and Engineering, 2024)
Internet of Things (IoT) devices are connected to the Internet and provide a variety of scopes in different projects and research domains. Smart home monitoring and automation largely depend on the usage of IoT devices. The concept of a smart home is now widely popular and a necessity in modern busy urban life. As most homeowner has to work at a distant workplace, it is a quite cumbersome job to monitor their household activity. In this paper, we address this issue and develop a prototype smart home system. The system contains IoT devices that are responsible for continuously sensing the home environment and sending the data to the Microcontroller. The microcontroller receives data and generates automated actions. We also connected the smart home system to a mobile Android application using the internet via a WiFi module. Thus, the homeowner can observe the current status of the home and will get a notification of the urgent situations in the application. We described the hardware requirement, software requirement, and connectivity of the devices. We ran different tests and checked the performance of the IoT sensors that were used. The developed prototype performed as expected and the integration of the smart home and Android application was quite smooth for monitoring and taking automated actions.GUB JOURNAL OF SCIENCE AND ENGINEERING, Vol 10(1), 2023 P 86-95